Comparison of the early and long-term results of aortic-coronary bypass surgery and percutaneous coronary intervention with new generation drug-eluting stents in diabetic patients with acute coronary syndrome - Shahane Elesgerli; Oktay Musayev; Shafa Shahbazova; Latife Kayıkçıoğlu; Kamran Musayev; Firdovsi Ibrahimov; Isfendiyar Ismayilov (Cukurova Medical Journal, 2020)
Purpose: The aim of this study was to determine the difference between patients undergoing coronary artery bypass graft (CABG) and percutaneous coronary intervention (PCI) (with new generation drug-eluting stents) who had diabetes mellitus during the course of an acute coronary syndrome (ACS). Materials and Methods: We carried out a retrospective evaluation of 405 diabetic patients admitted with an ACS during the period of 2 years in a single-center. Patients were followed for 5 years. All clinical incidents, such as death, cardiac death, myocardial infarction, stroke, revascularization, and stent thrombosis were recorded Results: We examined 405 patients with diabetes out of 1643 patients with ACS. Of these, 183 (45.1%) were included in the PCI group and 222 (54.8%) were in the CABG group. During 5-years follow-up, primary endpoints including death, MI, and stroke were observed in 31 patients (16.9%) in the PCI group and in 33 patients (14.9%) in the CABG group. There was no difference between the two groups in terms of primary endpoints. All-cause mortality during 5-years was observed in 17 patients (9.8%) in the PCI, 20 (9.1%) in the CABG group. Conclusion: There was no difference in all-cause mortality between the PCI and the CABG groups during 5-year follow-up. Repeated revascularization and myocardial infarction were higher in the PCI group and the stroke rates were higher in the CABG group.